A preliminary muscle activity analysis: Handle based and push-rim wheelchair propulsion - Babu Rajendra Kurup, N.; Puchinger, M.; Gfoehler, M. (Journal of Biomechanics, 2019)
Approximately ninety percent of the wheelchair users worldwide prefer the conventional push rim mode of propulsion for daily mobility and rehabilitation. Even though push-rim wheelchairs help to promote a healthy life style, the high muscular demand and the non-continuous push motions can lead to serious upper extremity injuries. In this study, muscle EMG data of ten healthy subjects were recorded for a newly introduced handle based propulsion mechanism (HBP) and compared to conventional push-rim propulsion at two workloads, 25 W and 35 W respectively. The results for the mean peak muscle activations at both workloads demonstrate that push-rim propulsion leads to higher peak muscle activity compared to HBP at a similar wheelchair forward velocity of 1.11 m/s. The generation of these high peak muscle activations with increasing loads in push-rim propulsion over time can lead to overuse injuries. Overall, the use of the HBP mechanism is less straining to the muscles and may reduce fatigue during prolonged propulsion.